Carbon footprint reduction for clinical waste management using cleaner production strategies at a selected Hospital / Noor Farah Hani Amir - Noor Farah Hani , Amir (2017)
Due to energy and material consumptions and waste produced, hospital operations generate high level of carbon footprint. In this study a detail analysis was done on carbon footprint generation from clinical waste and was assessed using cleaner production audit. University Malaya Medical Center (UMMC) was chosen as a case study for this purpose. It is estimated that the generation rate for clinical wastes is 0.99 kg per occupied bed per day, which translate into about 32 tons of CO2 per month. This is estimated based on actual total average clinical waste generated from various departments in 2016. Subsequently 17 major cleaner productions were generated and total reduction in carbon footprint and cost was also estimated. The implementation of these options can potentially reduce about 11% carbon footprints or at 0.88 kgCO2/bed/day (or reduction about 42 tons of CO2 per year). This reduction can also potentially reduce cost of operation by 11% (or RM 29,000 saving per month). This study proves that CP can be a strategy to reduce carbon footprint in hospitals and can be adapted by other hospital in Malaysia.